Effects of Dietary Phaffia rhodozyma Astaxanthin on Growth Performance, Carotenoid Analysis, Biochemical and Immune-Physiological Parameters, Intestinal Microbiota, and Disease Resistance in Penaeus monodon - Wang, Weilong; Liu, Mengting; Fawzy, Samia; Xue, Yucai; Wu, Meiqin; Huang, Xuxiong; Yi, Ganfeng; Lin, Qian (Frontiers in Microbiology, 2021)
The present study aimed to investigate the effect of dietary astaxanthin (Ast) from Phaffia rhodozyma on growth performance, survival, carotenoid content, the activity of antioxidant and immune-related enzymes, intestinal microbiota comparison, and disease resistance against Vibrio parahaemolyticus in Penaeus monodon. Juveniles (average weight 3.15 ± 0.12 g) were fed with six experimental diets supplemented with 0 (Control), 20.5, 41, 61.5, 82, and 102.5 mg/kg of Ast (defined as diet A-D) in triplicate for 56-days. The results indicated that shrimp fed with Ast supplementation significantly (P < 0.05) improved growth performance compared to the control. Further, significantly (P < 0.05) increased survival and decreased feed conversion ratio (FCR) demonstrated the beneficial effects of dietary Ast on enhancing nutrient utilization and ultimately improving the growth and survival of shrimp. Furthermore, shrimp fed with Ast including diet developed a deeper red color than the control, consistent with the significantly (P < 0.05) increased Ast deposition in the shrimp shell. Hemolymph-immunological parameters (aspartate aminotransferase AST, alanine aminotransferase ALT, and alkaline phosphatase AKP) and hepatopancreatic antioxidant status (total antioxidant capacity T-AOC, malondialdehyde MDA, catalase CAT, and superoxide dismutase SOD) were significantly (P < 0.05) affected by dietary Ast supplementation. Dietary increasing Ast levels significantly (P < 0.05) increased shrimp resistance performance to V. parahaemolyticus according to the LT50 results in the current study, which may be caused by increased total carotenoid contents in shrimp tissues from all the Ast supplemented treatments. Conversely, intestinal microbiota biodiversity and richness were not affected by dietary Ast. The best performances of growth, antioxidant status, immunological response, and carotenoid deposition were observed in diet E and F among all the Ast supplemented treatments. Overall, all the data suggested that dietary P. rhodozyma Ast played a critical role in improving growth performance, achieving the desired coloration, increasing carotenoid content, and keeping better health status of shrimp. Based on these positive performances, P. rhodozyma Ast could gain consumers’ trust as a natural source and provide a potential alternative for synthetic Ast using in the Penaeus monodon culture industry.